Factors related to dental health in 12-year-old children: a cross-sectional study in pupils Factors related to dental health in 12-year-old children: a cross-sectional study in pupils - Ernesto Smyth; Francisco Caamaño (Elsevier, 2005)
Objective: The aim of this study was to identify factors related to the prevalence of caries in 12-year-old schoolchildren. Methods: A cross-sectional study was carried out using a representative sample (n = 1217) of the population of 12-year-old schoolchildren in Galiza (northwest Spain). Independent variables were measured through a questionnaire, and dependent variables were determined through oral examination. Multiple and logistic regression were applied. Results: The decayed, missing and filled permanent teeth/decayed, filled primary teeth (DMFT-dft) value in the sample was 1.83 (95% confidence interval [CI], 1.67-1.98), the DMFT value was 1.53 (95% CI, 1.37-1.67), and the prevalence of caries was 61% (95% CI, 57.7-64.5). The prevalence of caries was directly related to a low frequency of brushing, greater use of toothpaste, and a higher consumption of sweets. The prevalence of caries was higher in rural than in urban areas. In contrast, the higher the mother's level of education and the greater the subject's knowledge of dental health, the lower the prevalence of caries. Conclusions: The main goals of dental health programmes should be to achieve quality brushing every day in children, to reduce the consumption of sweets, and to increase knowledge of dental health. Objetivo: Identificar los factores asociados a la prevalencia de caries en escolares de 12 años. Métodos: Estudio transversal sobre una muestra (n = 1.217) de escolares de 12 años de Galicia. Las variables independientes se midieron mediante un cuestionario y las dependientes, a través de exploración bucal. En el análisis estadístico se aplicaron regresión logística y regresión lineal múltiple. Resultados: El índice CAO-co en la muestra fue 1,83 (intervalo de confianza [IC] del 95%, 1,67-1,98), el índice CAO 1,53 (IC del 95%, 1,37-1,67), mientras que la prevalencia de caries se situó en el 61% (IC del 95%, 57,7-64,5). La prevalencia de caries estuvo directamente asociada a la baja frecuencia del cepillado, al mayor uso de pasta y al elevado consumo de golosinas. La prevalencia de caries determinada en el medio rural fue más alta que en el medio urbano. Por último, el mayor nivel de estudios de la madre y los mayores conocimientos sobre salud oral de los individuos se asocian a una menor prevalencia de caries. Conclusiones: A pesar de la moderada afectación por caries, los principales objetivos de los programas de salud oral para este grupo de edad deben ser: lograr el cepillado dental diario, reducir el consumo de golosinas e incrementar los conocimientos sobre salud oral. Por último, los programas de salud oral deben estar dirigidos principalmente a la población del medio rural y de menor nivel sociocultural.